2007
DOI: 10.1007/s10344-007-0161-8
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Anaplasma phagocytophilum and Rickettsia helvetica infection in free-ranging ungulates in central Slovakia

Abstract: The purpose of this study was to investigate the role of wild animals for Anaplasma phagocytophilum, other ehrlichiae/anaplasmae, Rickettsia helvetica and other rickettsiae and whether different genetic variants of A. phagocytophilum in central Slovakia exist. A total of 109 spleen samples from 49 red deer (Cervus elaphus), 30 roe deer (Capreolus capreolus), 28 wild boar (Sus scrofa) and two mouflon (Ovis musimon) were collected from June 2005 to December 2006. Polymerase chain reaction (PCR) amplification of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
28
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 24 publications
4
28
2
Order By: Relevance
“…Indeed, because positivity to pathogens is not only affected by the area of sampling but also by the host species from which ticks were collected, negative PCR results of this study could be due to the fact that ticks were not collected from wild boars, small rodents, or birds, which may act as either reservoirs or carriers of Borrelia spirochetes (Comstedt et al 2006;Gern 2008;Humair 2002;Juricová and Hubálek 2009;Matuschka et al 1992;Matuschka et al 1996) as well as A. phagocytophilum (Stefanidesova et al 2007) and spotted fever group rickettsiae (Schex et al 2011;Stefanidesova et al 2007). Furthermore, considering the involvement of several of the tick species collected as vectors of pathogens of zoonotic concern (e.g., Babesia spp., Coxiella burnetii, tick-borne encephalitis and Crimean-Congo haemorragic fever viruses) (Gray et al 1991;Hoogstraal 1979;Rehácek et al 1991;Rizzoli et al 2004), targeting a broader range of bacterial, rickettsial, protozoal and viral zoonotic tick-borne pathogen genes would also be advisable for future studies.…”
Section: Discussionmentioning
confidence: 80%
“…Indeed, because positivity to pathogens is not only affected by the area of sampling but also by the host species from which ticks were collected, negative PCR results of this study could be due to the fact that ticks were not collected from wild boars, small rodents, or birds, which may act as either reservoirs or carriers of Borrelia spirochetes (Comstedt et al 2006;Gern 2008;Humair 2002;Juricová and Hubálek 2009;Matuschka et al 1992;Matuschka et al 1996) as well as A. phagocytophilum (Stefanidesova et al 2007) and spotted fever group rickettsiae (Schex et al 2011;Stefanidesova et al 2007). Furthermore, considering the involvement of several of the tick species collected as vectors of pathogens of zoonotic concern (e.g., Babesia spp., Coxiella burnetii, tick-borne encephalitis and Crimean-Congo haemorragic fever viruses) (Gray et al 1991;Hoogstraal 1979;Rehácek et al 1991;Rizzoli et al 2004), targeting a broader range of bacterial, rickettsial, protozoal and viral zoonotic tick-borne pathogen genes would also be advisable for future studies.…”
Section: Discussionmentioning
confidence: 80%
“…The clinical symptoms are represented by sudden high fever, inappetence, lower production yield, weight loss and abortions in pregnant ewes (Scott et al 1991;Stuen 2007). In Slovakia, the presence of A. phagocytophilum was detected previously in ticks and wild living animals (Šte-fančíková et al 2008;Štefanidesová et al 2008;Víchová et al 2010). Recent study also confirmed its circulation in sheep flocks (Derdáková et al 2011).…”
Section: Introductionmentioning
confidence: 92%
“…The most common infection in the current study was A. phagocytophilum, with a prevalence of 37%. In Europe, it is believed that cervids are the main reservoir hosts of these bacteria, having been found commonly in roe deer in Spain (18%; de la Fuente et al 2008), Switzerland (18%; Liz et al 2002), Slovenia (85%; Petrovec et al 2002), Slovakia (50%; Stefanidesova et al 2008), and Austria (43%; Polin et al 2004). In Poland, prevalence of this species has been reported to range from 9% to 38% in different regions of the country (Adamska and Skotarczak 2007, Michalik et al 2009, Hapunik et al 2011).…”
Section: Discussionmentioning
confidence: 99%